Clinical manual of substance abuse - Kinney, Jean, 1943- (St. Louis : Mosby, 1996)
A comprehensive practical reference for all health care professionals who care for patients with substance abuse problems. Part I provides a framework for clinical management of these patients and Part II is comprised of chapters on working with specific populations and groups
Overview of substance use and abuse / Donald A. West, Jean Kinney -- Routine screening and initial assessment / Patrick G. O'Connor -- Engaging the patient in treatment / Patrick G. O'Connor -- Substance use treatment / Jean Kinney, Donald A. West -- Medical management / John Severinghaus, Jean Kinney -- Nursing care of the substance-abusing patient / Nancy B. Fisk, Paula Ruth -- Social work perspectives on alcohol and drug abuse problems / Shulamith Lala Ashenberg Straussner, Christine Huff Fewell -- Educating yourself and others / Jean Kinney. Resources for educators and trainers / Jean Kinney -- African Americans / Omowale Amuleru-Marshall -- Hispanics / Patrick J. Abbott, Margie Trujillo -- Migrant workers / Kimberly Palma -- Native Americans / Jean Kinney -- Rural residents / Allan W. Graham -- Dual diagnosis / Fred C. Osher -- Effects of prenatal alcohol and drugs / Ann P. Streissguth, Loretta P. Finnegan -- Children of alcoholics / Heather J. Gotham, Kenneth J. Sher -- Adolescents / Stuart A. Copans, Jean Kinney -- College students and campus programs / Jean Kinney. Women / Susan McGrath Morgan, Jean Kinney -- Elderly / Wendy I. Adams, Jean Kinney -- Impaired health care professionals / Jean Kinney
Includes bibliographical references and index.
Keywords: Substance abuse -- Treatment; Substance Abuse -- therapy; Alcoholism -- therapy